Transformasi Pembelajaran Akuntansi: Dampak Perubahan Berbasis Tradisional ke Digital Terhadap Prestasi Belajar Siswa - Sutiana, Dian; Suranto, Suranto (PAKAR Pendidikan, 2025)
The development of technology, particularly in the field of education, plays a strategic role in enhancing the quality of learning and student achievement. This research focuses on digital transformation in accounting education at vocational schools in Surakarta, exploring how the application of technology can support the improvement of student learning outcomes. The research approach is qualitative, with data collected through in-depth interviews and direct observations at three schools: SMK Negeri 1 Surakarta, SMK Negeri 3 Surakarta, and SMK Negeri 6 Surakarta. The research informants include 8 teachers and 6 students from the Accounting program. The results indicate that the implementation of digital technology in the accounting learning process has transformed teaching methods to be more innovative and interactive. This not only enhances students' understanding of accounting concepts but also motivates them to be more active in their learning. Furthermore, this digital transformation positively impacts the mastery of technical skills, such as the use of modern accounting software relevant to industry needs. Student achievement has shown improvement in both academic aspects and practical skills. Overall, this research underscores that the integration of technology in education can serve as an important catalyst in supporting learning success and preparing students for the workforce.